2020
DOI: 10.18510/hssr.2020.83108
|View full text |Cite
|
Sign up to set email alerts
|

Do Innovation and Entrepreneurship Have Dominant Roles in Economic Growth? A New Perspective of Developed Countries

Abstract: Purpose of the study: The purpose of this paper is to analyze the potential causal link between innovation, entrepreneurship activity, and economic growth in the case of nine developed countries over the time-span ranging between 2001 and 2014. The research goal is to examine if the findings of this paper support the endogenous growth theory. Methodology: This paper has initially explored the stationary properties of the variables. Moreover, the causal links between the variables of interest have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Regression analysis was applied for the examination, and findings revealed that in comparison with the significant negative impact of conformity to rich villagers, conformity to relatives, neighbors, and village cadres all have a positive influence on households' willingness to adopt energy utilization of crop straw exampled by biogas (Zeng et al, 2019). In their work, Satrovic et al (2020) examined and found a positive and driving effect of innovation on economic development, which is expected to reduce environmental degradation.…”
Section: Survey Of Recent Literaturementioning
confidence: 99%
“…Regression analysis was applied for the examination, and findings revealed that in comparison with the significant negative impact of conformity to rich villagers, conformity to relatives, neighbors, and village cadres all have a positive influence on households' willingness to adopt energy utilization of crop straw exampled by biogas (Zeng et al, 2019). In their work, Satrovic et al (2020) examined and found a positive and driving effect of innovation on economic development, which is expected to reduce environmental degradation.…”
Section: Survey Of Recent Literaturementioning
confidence: 99%